HAND HYGIENE IN PATIENT CARE - GÜNTER Kampf (Фундаментальная и клиническая медицина, 2018)
Hand hygiene is an essential element to reduce the transmission of nosocomial pathogens in healthcare facilities. The WHO has launched a global campaign on hand hygiene with the aim to reduce healthcare-associated infections. Hand disinfection using alcohol-based hand rubs is the treatment of choice for clean hands according to the five indications for hand hygiene. The dermal tolerance is usually good when emollients are part of the formulation. Hand washing should be an exception, e.g. when hands are visibly soiled or contaminated with bacterial spores such as C. difficile. Use of plain liquid soap is usually sufficient, antimicrobial soaps do not provide a relevant advantage over plain soaps. Preoperative treatment of hands is ideally done with alcohol-based hand rubs. Additional biocidal agents with a persistent antimicrobial activity are not necessary and may cause skin irritation, allergic reactions or biocidal tolerance. Surgical scrubbing with an-timicrobial soaps is more and more replaced by surgical hand rubbing which is faster (often 1.5 min application time) and more gentle to the skin. Following the WHO recommendations will help to prevent health-care-associated infections and to reduce the occupa-tional stress to the skin of healthcare workers.